Environmental Commitment: Faktor Fundamental pada Environmental Entrepreneurship - Rr. Tur Nastiti (Universitas Kristen Maranatha, 2004)
Natural environment consideration becomes a new critized source of stakeholders in their organizations. In order to become organizations that have responsibility on environmental perspectives, organizations tend to synergize environmentalism and entrepreneurship. Entrepreneurs are typically described as individuals who perceive a vision, commit themselves to that vision, and almost single handedly carry the vision to its successfull implementation. The aim of this article is to analyze the role of environmental commitment to environmental entrepreneurship. The conclusion describe that commitment is a basis for entrepreneurship and that relationship has a positive contribution's strategy.